Bleeding women and theology from below: How Mark’s narrative of the indignity of the bleeding woman serves as a model of transgressive resistance for the "violent" contemporary South African Student Protest Movement - Brown, Alease (Stellenbosch Theological Journal, 2021)
Dishonour is heaped upon dishonour for those who have been deprived of material conditions for life, often due to historical legacies of racialized inequality and oppression. Rather than villainizing those engaged in protests that produce disorder and defacement, identifying and articulating the sacredness of seemingly profane aspects of such contemporary movements is a singular and imperative task of Christian theology today. Through a close reading of the narrative of the bleeding woman in Mark's Gospel, this essay argues that the South African student protest movement of 2015-2016, which included regular eruptions of destructive physical force, is an example of activism that represents the Gospel's injunctions towards the securing of dignity by the marginalized unheard and unhelped. First, the essay will discuss the milieu of honour/shame which pervaded the first-century Palestinian context of the Gospels. Following this, the essay undertakes a close reading of the biblical narrative of the bleeding woman in Mark's Gospel. It will be demonstrated that the womanâ's intentional transgression of the social order resulted in her approbation by Jesus.